Toxicities and Quality of Life during Cancer Treatment in Advanced Solid Tumors - Eun Mi Lee; Paula Jiménez-Fonseca; Rocio Galán-Moral; Sara Coca-Membribes; Ana Fernández-Montes; Elena Sorribes; Esmeralda García-Torralba; Laura Puntí-Brun; Mireia Gil-Raga; Juana Cano-Cano; Caterina Calderon (Current Oncology, 2023)
The purpose of the study was to identify subgroups of advanced cancer patients who experienced grade 3–4 toxicities as reported by their oncologists as well as identify the demographic, clinical, and treatment symptom characteristics as well as QoL outcomes associated with distinct profiles of each patient. A prospective, multicenter, observational study was conducted with advanced cancer patients of 15 different hospitals across Spain. After three months of systemic cancer treatment, participants completed questionnaires that evaluated psychological distress (BSI-18), quality of life (EORTC QLQ-C30) and fatigue (FAS). The most common tumor sites for the 557 cancer patients with a mean age of 65 years were bronchopulmonary, digestive, and pancreas. Overall, 19% of patients experienced high-grade toxicities (grade 3–4) during treatment. Patients with recurrent advanced cancer, with non-adenocarcinoma cancer, undergoing chemotherapy, and a showing deteriorated baseline status (ECOG > 1) were more likely to experience higher toxicity. Patients who experienced grade 3–4 toxicities during cancer treatment had their treatment suspended in 59% of the cases. Additionally, 87% of the patients had a dose adjustment or a cycle delayed in their treatment due to a high risk of dying during treatment. Future research should focus on identifying interventions to reduce high-grade toxicities and improve quality of life in cancer patients.